Assessment of psychometric properties of the self-stigma inventory for Iranian families of persons who use drugs - Dinmohammadi, Mohammadreza; Jalali, Amir; Naderipour, Arsalan (Frontiers in Public Health, 2022)
Background: Substance use disorder (SUD) and related problems take a toll on the individual, family, and society. This study was conducted to determine the psychometric properties of the self-stigma scale in the families of Persons Who Use Drugs (PWUDs) in Iran. Methods: The above study is a methodological and psychometric study. The study population consisted of 311 family members of PWUDs visiting outpatient and inpatient addiction treatment centers in Kermanshah who were selected using convenience sampling. The 14-item Yildiz et al. Self-Stigma Inventory for Families (SSI-F), which was developed in 2019 using interviews and scales connected with stigma was applied. The ten steps developed by Wilde et al. were used in this study for cultural validation. The exploratory factor analysis (EFA) (140 samples) and confirmatory factor analysis (CFA) (311 subjects) were used to confirm the construct validity, and the test-retest method was used to confirm the reliability of tools. Cronbach’s alpha was also used to test the internal consistency of tools. Findings: The results of EFA and CFA scales in families of PWUDs were confirmed with three factors and 14 items. The reliability degree of the tools was confirmed as 0.891 and the Cronbach’s alpha was confirmed as 0.879 using the test-retest method. Pearson’s correlation coefficient indicated a positive and significant status between the scale’s items/factors and the scale itself. Conclusion: Generally, the results showed that PWUDs SF-I scale in Iranian families was valid and reliable with three factors and 14 items, and it can be used to conduct relevant studies.